Cancer Microenvironment and Inflammation: Role of Hyaluronan - Nikitovic, Dragana; Tzardi, Maria; Berdiaki, Aikaterini; Tsatsakis, Aristidis; Tzanakakis, George N. (Frontiers in Immunology, 2015)
The role of inflammation in the development of cancer was described as early as 19th century. Abundant evidence supports the preposition that various cancers are triggered by infection and chronic inflammatory disease whereas, evading immune destruction has been proposed as one of the new “hallmarks of cancer.” Changes of the tumor microenvironment have been closely correlated to cancer-mediated inflammation. Hyaluronan (HA), an important ECM component, has become recognized as an active participant in inflammatory, angiogenic, fibrotic, and cancer promoting processes. This review discusses how HA and specific HA-binding proteins participate in and regulate cancer-related inflammatory processes.